SISTEM INFORMASI PADA â€œMAYAâ€ WEDDING ORGANIZER BERBASIS WEBSITE - Imam Rosyadi; Arum Sari (Universitas Muhammadiyah Pekajangan Pekalongan, 2018)
Maya Wedding Organizer offers reservation system by directly coming to the office. On the other hand, the dissemination of information is through man to man, leaflets and brochures. Itâ€™s very troublesome, because it makes the dissemination of information is very limited and ordering process canâ€™t be done from any place. To solve the problem, we need to make an order information system that can be used for data management processes, realted to the process of ordering wedding organizer as well as the dissemination of information to the media. In Information System Based of Website â€œMayaâ€ wedding organizer, the author uses the waterfall system development. The waterfall method has many steps such as requirements analysis and specification, design, coding and testing, integration and system testing, maintenance. The information system has two user, i.e admin, and consumers. The ability of these systems is to accommodate ordering data and can be used for disseminate information about products of Maya Wedding Organizer. Report the results of this system is an order by a certain time. Keywords: System Information, Wedding Organizer, Maya Wedding Organizer and Ordering Abstrak Proses pemesanan di Maya Wedding Organizer saat ini masih dengan datang langsung ke kantornya. Penyebaran informasi produk yang dimiliki juga masih melalui orang ke orang, leaflet dan brosur. Hal tersebut sangat merepotkan, karena membuat penyebaran informasi sangat terbatas dan proses pemesanan tidak bisa dilakukan dari dimanapun dan kapanpun.Untuk mengatasi masalah tersebut, perlu dibuat sebuah sistem informasi pemesanan yang dapat digunakan untuk proses pengelolaan data yang berkaitan dengan proses pemesanan wedding organizer sekaligus untuk media penyebaran informasi. Dalam pembuatan Sistem Informasi Maya Wedding Organizer Berbasis Website ini, penulis menggunakan metode pengembangan sistem waterfall. Secara garis besar metode waterfall mempunyai langkah - langkah yaitu requirements analysis & specification, design, coding and testing, integration and system testing, maintenance. Sistem informasi ini memiliki dua user yaitu admin, pelanggan. Kemampuan sistem ini diantaranya dapat menampung data pemesanan dan dapat digunakan untuk penyebaran informasi produk-produk Maya Wedding Organizer. Hasil sistem ini adalah laporan order dengan waktu tertentu. Kata Kunci: Sistem Informasi, Wedding Organizer, Maya Wedding Organizer dan Pemesanan